Confirmation of the single-step membrane filtration procedure for estimating Pseudomonas aeruginosa densities in water. - Dutka, B J (1977)
The efficiency of two procedures, membrane filtration and most probable number, to resuscitate and enumerate Pseudomonas aeruginosa have been compared at two temperatures and varying incubation periods. Data indicate that the membrane filtration procedure using mPA or mPA medium B is more efficient than the most-probable-number procedure in estimating P. aeruginosa populations. It was also found that the specificity of the membrane filtration procedure was such that 92 to 99% of the colonies counted as P. aeruginosa were confirmed, whereas only 2.7 to 10% of the nontypical colonies were confirmed as P. aeruginosa. Furthermore, the data indicate that mPA medium B combined with a 3- to 4-day incubation period at 4.15 degrees C is slightly more specific than mPA medium and is a valid single-step procedure for the resuscitation and enumeration of P. aeruginosa from water or sewage effluent.